2014
DOI: 10.1002/2013wr014290
|View full text |Cite
|
Sign up to set email alerts
|

A new method for verification of delineated channel networks

Abstract: Several methods are used to delineate channel networks. The most widely used are the contributing area method, area-slope method, and grid network ordering method. The number of delineated channels depends on the threshold adopted when using each method. However, the appropriate threshold value required to delineate channel networks, and their corresponding accuracies, are still uncertain. The consistency between the delineated channels and actual channels can be evaluated by carrying out extensive field surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…A simpler method was used by Omran, Dietrich, Abouelmagd, and Michael (2016), who computed the root mean squared distance between stream order results. Liu, Khan, and Sharma (2014) noted the lack of appropriate measures for assessing the accuracy of delineated channel networks and proposed a procedure based on analysing the cross-sections of all delineated channels and determining the corresponding incision index.…”
Section: Prediction Of Channel Headsmentioning
confidence: 99%
“…A simpler method was used by Omran, Dietrich, Abouelmagd, and Michael (2016), who computed the root mean squared distance between stream order results. Liu, Khan, and Sharma (2014) noted the lack of appropriate measures for assessing the accuracy of delineated channel networks and proposed a procedure based on analysing the cross-sections of all delineated channels and determining the corresponding incision index.…”
Section: Prediction Of Channel Headsmentioning
confidence: 99%
“…Montgomery and Dietrich (1992) showed that a specific topographic threshold in the field is related to the channel header locations. Liu et al (2014) proposed a new method with three incision indices incised channel index, partially incised channel index and non-incised channel index. Channel cross-section analysis method is used to determine the incision indices were verified against RGB images of the areas.…”
Section: Introductionmentioning
confidence: 99%